Fall Prevention: Home Safety Inventory - Leigh Ann Martin (EDIS)
Homes you’ve lived in most of your life can cause problems as you age. Use this inventory to find possible problem areas. Skip any that don’t apply to you. If you answer “no” to any of the questions, make the needed change(s) as soon as possible. This document is FCS2229, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: April 2005.